Biotechnological application of Cyanobacteria in, Agriculture, Medicine and Environment - Tadesse, Tefera (International Journal of Aquaculture Research and Development, 2022)
Cyanobacteria are considered as one of the important group of organisms having significant ecological, industrial, and biotechnological importance. Cyanobacteria have gained a lot of atten ion in recent years because of their potential applications in biotechnology. This review presents an overview of uses of cyanobacteria in industry agriculture, environment pharmaceutical and medicinal roles and to provide future prospects of the field of cyanobacteria biotechnology. Nowadays cyanobacteria have gained attention researchers because of their various potential applications such as food and feed pharmaceutical industries in medicine, in bioremediation, soil conditioning, as biopolymers, bio adhesives, bioenergy and biofertilizers. Due to presence of wide spectrum of bioactive compounds cyanobacteria has possesses antiviral, antibacterial, antifungal and anticancer activities. Several strains of cyanobacteria are also rich in food supplements. Further nitrogen fixing and soil conditioning capacity of cyanobacteria attracted researchers. Recent studies have also shown that cyanobacteria have capability to degrade environmental pollutants and are also being used as a promising source of alternative energy. Cyanobacteria has also its limitations through bloom production it influnces on the nutrient availability and usage of phytoplankton plants. This review is an effort to forward the valuable information about the qualities of cyanobacteria and their potential role in solving the agricultural and environmental problems for the future welfare of the planet.Thus more efforts should be made in search of more potential strains of cyanobacteria to ensure maximum production of the desired products.
Keywords: Cyanobacteria Bioremediations; Nitrogen fixation; Biological Metabolites; Microcystin eutrophication